2022
DOI: 10.1002/chem.202203341
|View full text |Cite
|
Sign up to set email alerts
|

Nonsymmetric [Pt(C^N*N′^C′)] Complexes: Aggregation‐Induced Emission in the Solid State and in Nanoparticles Tuned by Ligand Structure

Abstract: Invited for the cover of this issue are the groups of Sergey P. Tunik and his colleagues from St Petersburg University. The image depicts the strong bathochromic shift of the emission wavelength of phosphorescent platinum(II) complexes upon their aggregation in the presence of water. Read the full text of the article at 10.1002/chem.202202207.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…In this series, the Ir2-NO 2 gives a record QY value of 81% in degassed solution that is a result of the lowest k nr and highest k r ; the latter may be explained by a very high contribution of metal orbitals in the emissive T 1 →S 0 transition ( Table S13 ) and, consequently, higher magnitude of spin-orbital constant, which facilitates the spin-forbidden transition. The complexes with benzothienyl moiety coordinated to iridium center (Ir4-F and Ir4-NO 2 ) display a large bathochromic shift of emission band maxima to the NIR region, up to 792 nm in the case of Ir4-NO 2, that is typical for the ligands containing this metalated aromatic system [ 11 , 26 , 29 , 30 ]. Emission efficiency for both complexes demonstrated extremely strong reduction that did not allow reliable determination of the quantum yield values.…”
Section: Resultsmentioning
confidence: 99%
“…In this series, the Ir2-NO 2 gives a record QY value of 81% in degassed solution that is a result of the lowest k nr and highest k r ; the latter may be explained by a very high contribution of metal orbitals in the emissive T 1 →S 0 transition ( Table S13 ) and, consequently, higher magnitude of spin-orbital constant, which facilitates the spin-forbidden transition. The complexes with benzothienyl moiety coordinated to iridium center (Ir4-F and Ir4-NO 2 ) display a large bathochromic shift of emission band maxima to the NIR region, up to 792 nm in the case of Ir4-NO 2, that is typical for the ligands containing this metalated aromatic system [ 11 , 26 , 29 , 30 ]. Emission efficiency for both complexes demonstrated extremely strong reduction that did not allow reliable determination of the quantum yield values.…”
Section: Resultsmentioning
confidence: 99%
“…Compound 8 was prepared following a slightly modified published procedure. 39 To a solution of bromopyrimidine 6 (139 mg, 0.35 mmol) and N -phenylpyridin-2-amine (51 mg, 0.30 mmol) in toluene (8 mL), t -BuOK (45 mg, 0.4 mmol), dppf (11 mg, 20 μmol) and Pd 2 (dba) 3 (9.2 mg, 10 μmol) were added under an Ar atmosphere. The reaction mixture was stirred at for 1 d at 110 °C (oil-bath temperature).…”
Section: Methodsmentioning
confidence: 99%
“…2C). 56 In the same year, Zhang et al reported a rigid oxygen-bridged p-menthane-modified tetradentate cyclometalated platinum(II) complex (Pt12). 16 Pt12 exhibited significant aggregation-enhanced emission (AEE) in a DMSO/H 2 O mixture (5 Â 10 À5 mol L À1 ) with a high PLQY of 73.2%.…”
Section: Platinum Complexes With Aggregation-induced Emissionmentioning
confidence: 99%